Risk assessment of polycyclic aromatic hydrocarbons and heterocyclic aromatic amines in processed meat, cooked meat and fish-based products using the margin of exposure approach - Ab-Latif, Nurin Irdina; Abdullah, Rozaini; Omar, Syaliza; Sanny, Maimunah (Penerbit Universiti Sains Malaysia, 2024)
Background: The objective of this study is to assess the risk of exposure of polycyclic aromatic hydrocarbons (PAHs) and heterocyclic aromatic amines (HCAs) in meat and fish-based products marketed in Malaysia using the margin of exposure (MOE) approach. Methods: Benchmark Dose (BMD) software was used to model the BMD at a lower end of a one-sided 95% confidence interval with a 10% incremental risk (BMDL10) of PAHs and HCAs from different target organ toxicities. The MOEs of PAHs and HCAs in meat and fish-based products were determined by utilising the calculated BMDL10 values and estimated daily intake of meat and fish-based products from published data. Results: The calculated BMDL10 values of PAHs (i.e. benzo[a]pyrene [BaP] and fluoranthene [FA]) and HCAs (i.e. 2-amino-3,8,dimethylimidazo[4,5-f]quinoxaline [MeIQx] and 2-amino-1-methyl-6-phenylimidazo[4,5,6]pyridine [PhIP]) ranged from 19 mg/kg bw/day to 71,801 mg/kg bw/day. The MOE of BaP ranged from 41,895 to 71,801 and that of FA ranged from 19 to 1412. As for MeIQx and PhIP, their MOEs ranged from 6,322 to 7,652 and from 2,362 to 14,390, respectively. Conclusion: The MOEs of FA, MeIQx and PhIP were lower than 10,000, indicating a high concern for human health and therefore demanding effective risk management actions.